Modular curriculum : support subject outline for life coping skills training handbook (IADB Regional Project Office KingstonJM, 2000)
Deals with topics such as work disciplines; workplace rules, behaviour and relationships; and, communicating, producing and coping at work.
Keywords: PERSONALITY DEVELOPMENT